Rescue - Haas, Jessie (Boyds Millls Press, an imprint of Highlights, 2018)
When Chess moves near Joni, their differing opinions have Joni defending her family's farm, and she must find the courage to stand up to Chess when she decides to "rescue" the miniature horses from a nearby farm.